2017
DOI: 10.1039/c7ra02301d
|View full text |Cite
|
Sign up to set email alerts
|

Design of efficient mono-aminosilane precursors for atomic layer deposition of SiO2 thin films

Abstract: The suitability of six mono(alkylamino)silane precursors for growing SiO2 films via ALD is assessed with DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“… 34 These theoretical results were confirmed experimentally by Peña et al who employed infrared adsorption spectroscopy to study DSBAS adsorption on −OH sites and demonstrated the formation of −SiH 3 species on the surface after the precursor exposure. 35 , 36 …”
Section: Concise Overview On the Ald Reaction Mechanism Of Sio 2 Using Aminosilane Precursorsmentioning
confidence: 99%
“… 34 These theoretical results were confirmed experimentally by Peña et al who employed infrared adsorption spectroscopy to study DSBAS adsorption on −OH sites and demonstrated the formation of −SiH 3 species on the surface after the precursor exposure. 35 , 36 …”
Section: Concise Overview On the Ald Reaction Mechanism Of Sio 2 Using Aminosilane Precursorsmentioning
confidence: 99%
“…A recent report used density functional theory to model the dissociative chemisorption of silicon nitride precursors (mono(alkylamino)silanes) on silicon dioxide to determine the effect of different aminoalkyl ligands. 118 Adsorption energies, driven primarily by hydrogen bonding did not vary significantly with size of aminoalkyl ligands, however, a large variation in the reaction energy barriers was observed with ligand size due to transition state interactions and steric effects. The ALD window for suitable thin film growth was found to be widest for diisopropylaminosilane (DIPAS) and dipropylaminosilane (DPAS) precursors (∼100…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
“…First, we investigated the growth per cycle (GPC) of ALD SiO 2 films at 100 °C, which is the lowest temperature for its ALD window, as a function of DIPAS and O 3 exposure times (Figure S2, Supporting Information). [ 36 ] Optimized exposure times to DIPAS and O 3 were determined to be 3 and 6 s, respectively, indicating a self‐saturated GPC of ≈0.82 Å/cycle. N 2 purging time following both DIPAS exposure and O 3 exposure was maintained at 60 s, which we found was sufficient to avoid unwanted chemical reactions between the precursor and co‐reactant.…”
Section: Resultsmentioning
confidence: 99%